2008
DOI: 10.2136/vzj2007.0114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Soil Hydraulic Conductivity Drop Using a Three‐Dimensional Root Water Uptake Model

Abstract: The coupling of soil and root water fluxes at the plant scale is a particularly challenging task. Numerical three‐dimensional plant‐scale models exist that consider these soil–root interactions. The influence of the hydraulic conductivity drop at the microscopic scale and especially the effect on root water uptake is not yet assessed in such models. In this study, an analytical approach describing the hydraulic conductivity drop from the bulk soil to the soil–root interface for a three‐dimensional plant‐scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 20 publications
(34 reference statements)
2
51
0
Order By: Relevance
“…In many circumstances, a more robust root system with increased root length or root biomass has been considered a positive feature under drought conditions (de Dorlodot et al, 2007;Tardieu, 2012). For example, in fields with deep soil, increased root biomass and length would enable plants to reach deeper soil layers and explore a wider soil area, thus leading to more water and nutrient uptake Schroder et al, 2008;Tardieu, 2012). However, new plant cultivars with enhanced drought tolerance generated in several breeding programs exhibited decreased root biomass (Bolaños and Edmeades, 1993;Bruce et al, 2002;Campos et al, 2004;Tardieu, 2012).…”
Section: Root Architecture and Plant Abiotic Stress Tolerancementioning
confidence: 99%
“…In many circumstances, a more robust root system with increased root length or root biomass has been considered a positive feature under drought conditions (de Dorlodot et al, 2007;Tardieu, 2012). For example, in fields with deep soil, increased root biomass and length would enable plants to reach deeper soil layers and explore a wider soil area, thus leading to more water and nutrient uptake Schroder et al, 2008;Tardieu, 2012). However, new plant cultivars with enhanced drought tolerance generated in several breeding programs exhibited decreased root biomass (Bolaños and Edmeades, 1993;Bruce et al, 2002;Campos et al, 2004;Tardieu, 2012).…”
Section: Root Architecture and Plant Abiotic Stress Tolerancementioning
confidence: 99%
“…Following the mass conservation principle, the flux density of water (motion speed) increases as it gets closer to the root surface, and, in parallel, its water potential decreases as well as the soil conductivity. The rhizosphere is thus susceptible to a local drop of hydraulic conductivity that is favored by high rates of root water uptake and by soil properties, such as coarse textures, that steepen the relationship between soil conductivity and water potential (Shroeder et al, 2008). Soil hydraulic properties and water potential around each root segment therefore set a maximum uptake rate above which a soil restriction to water flow is likely to occur.…”
Section: Influence Of the Soil Water Distributionmentioning
confidence: 99%
“…Schröder et al (2008) has shown, that the local soil hydraulic conductivity drop around the roots becomes important when increasing the size of the bulk soil grid cells. We accounted for this by implementing a microscale radial flow model coupled to the bulk soil water flow.…”
Section: Discussionmentioning
confidence: 99%